2022
DOI: 10.3389/fphys.2022.989601
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory protein 4 is required for Bradysia odoriphaga to be olfactory attracted to sulfur compounds released from Chinese chives

Abstract: Bradysia odoriphaga (Diptera: Sciaridae) is a serious pest of Chinese chives cultivated in China. Chemosensory proteins (CSPs) are important components of insect olfactory systems that capture and bind environmental semiochemicals which are then transported to olfactory receptors. Despite their importance, the mechanism of olfaction and related behavioral processes in B. odoriphaga have not been characterized. Here, we found that BodoCSP4 has an important olfactory function. RT-qPCR indicated that BodoCSP4 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The 3D model of CrufCSP1 revealed that it consists of four α-helices and four conserved cysteine residues, forming a hydrophobic pocket. This is different from other insect CSPs, which typically have five [54,55] or six α-helices [56,57]. We speculate that the CrufCSP1 has fewer α-helices, as this might lead to the formation of a larger hydrophobic pocket in its spatial conformation, making it more conducive to the entry of odor molecules and the formation of stable complexes.…”
Section: Discussionmentioning
confidence: 67%
“…The 3D model of CrufCSP1 revealed that it consists of four α-helices and four conserved cysteine residues, forming a hydrophobic pocket. This is different from other insect CSPs, which typically have five [54,55] or six α-helices [56,57]. We speculate that the CrufCSP1 has fewer α-helices, as this might lead to the formation of a larger hydrophobic pocket in its spatial conformation, making it more conducive to the entry of odor molecules and the formation of stable complexes.…”
Section: Discussionmentioning
confidence: 67%
“…One of the CSP transcripts was highly expressed in both sexes and female biased (Table S6: D). Interestingly, in Bradysia odoriphaga Winnertz, 1867 (Diptera: Sciaridae), a CSP was associated with detection of sulfur-rich compounds [ 87 ], which are common attractants for blowflies [ 16 ]. Two TRPs were male biased (Table S6: K); however, the expression of these receptors was very low.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Yang et al found that the knockdown of BodoCSP4 in B. odoriphaga altered the preference for diallyl disulfide and nheptadecane. 48 Similarly, Maleszka et al reported that silencing AmelCSP5 in A. mellifera resulted in changes in embryonic development. 21 In R. padi, Peng et al demonstrated that knockdown of RpCSP4 and RpCSP6 significantly increased aphid mortality under sublethal concentrations of imidacloprid.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Yang et al found that the knockdown of BodoCSP4 in B. odoriphaga altered the preference for diallyl disulfide and n-heptadecane . Similarly, Maleszka et al reported that silencing AmelCSP5 in A.…”
Section: Discussionmentioning
confidence: 99%